2017
DOI: 10.2298/fil1704913d
|View full text |Cite
|
Sign up to set email alerts
|

Vertices of paths of minimal lengths on suborbital graphs

Abstract: The Modular group ? acts on the set of extended rational numbers ?Q transitively. Here, our main purpose is to examine some properties of hyperbolic paths of minimal lengths in the suborbital graphs for ?. We characterize all vertices of these hyperbolic paths in the suborbital graphs which are trees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…Theorem 2.1. [4] If (u, N) = 1, then exist an integer t such that u 2 + tu + 1 ≡ 0 (mod N), for t ≥ 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Theorem 2.1. [4] If (u, N) = 1, then exist an integer t such that u 2 + tu + 1 ≡ 0 (mod N), for t ≥ 2.…”
Section: Resultsmentioning
confidence: 99%
“…In [3] and [8], the results are extended. The definition of minimal length path for F u,N suborbital graphs is given by Deger in [4]. In [4], it has been showed that; there is a integer t, which provides u 2 + tu + 1 ≡ 0 (mod N) congruence equation for F u,N suborbital graphs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elliptic elements and elliptic circuits are investigated in [6]. In [7], it is shown that each vertex in the suborbital graph F u,N has a continued fraction structure for (u, N ) = 1 and u ≤ N and investigated the vertices on path with minimal lengths. Suborbital graphs are studied for invariant groups in [8].…”
Section: Introductionmentioning
confidence: 99%